Genetic diversity of the haemagglutinin (HA) of human influenza a (H1N1) virus in montenegro: Focus on its origin and evolution. Issue 11 (25th April 2016) - Mugosa, Boban; Vujosevic, Danijela; Ciccozzi, Massimo; Valli, Maria Beatrice; Capobianchi, Maria Rosaria; Lo Presti, Alessandra; Cella, Eleonora; Giovanetti, Marta; Lai, Alessia; Angeletti, Silvia; Scarpa, Fabio; Terzić, Dragica; et al.
Abstract : In 2009 an influenza A epidemic caused by a swine origin H1N1strain, unusual in human hosts, has been described. The present research is aimed to perform the first phylogenetic investigation on the influenza virus A (H1N1) strains circulating in Montenegro, from December 1, 2009, when the first case of death due to H1N1 was confirmed, and the epidemic began causing a total of four fatalities. The phylogenetic analysis of the strains circulating showed the absence of a pure Montenegrin cluster, suggesting the occurrence of multiple re‐introductions in that population from different areas till as far as the early 2010. The time to most recent common ancestor (TMRCA) for the complete dataset has been dated in early 2008, pre‐dating the first Montenegrin identification of H1N1 infection. These data suggest that virus was spreading undetected, may be as a consequence of unidentified infections in returning travelers. Anyhow, the estimated TMRCA of Montenegrin strains is fully consistent to that found in different areas. Compatibly with the time coverage of the study period here analyzed, molecular dynamic of Montenegrin strains follows similar trend as in other countries. J. Med. Virol. 88:1905–1913, 2016 . © 2016 Wiley Periodicals, Inc.